Focus Research Entrepreneurship Learning and Entrepreneurship Intention: A Systematic Review - Fadli Agus Triansyah; Resti Ramadhaniyati; Kartika Dwi Pratiwi Siregar (Universitas 17 Agustus 1945, 2023)
Entrepreneurship learning is the process of acquiring knowledge and skills related to entrepreneurship, including the ability to recognise and develop new business opportunities, effectively manage resources, and take calculated risks in order to achieve success in business ventures often associated with intentional entrepreneurship refers to a person's motivation or inclination to launch a new business venture. The focus of this study is on entrepreneurial learning and intention, and it employs a systematic review methodology from 2021 to 2023 scopus database. The focus of research related to entrepreneurship learning and entrepreneurship intention focuses on several things such as experiential learning practice, individual characteristics such as gender, age, proximity to entrepreneurship, academic performance, previous work experience, and propensity for risk and observe the change, innovation, one-day female-focused STEM-based entrepreneurship program, entrepreneurial self-efficacy, young employees’ perception of their current paid jobs, creativity among female learners, cognitive and social conditions, creative self-efficacy, and theory of planned behavior.